Alternative proteins: an innovative approach to dog food production - Carrillo-Huerta, Yolanda D.; Gutiérrez-Chávez, Abner. J.; Pérez-Zavala, Ma. de L.; Casados-Vázquez, Luz E.; Barboza-Corona, José E. (Frontiers in Animal Science, 2025)
In recent years, the search for alternative proteins for pet consumption has increased due to concerns about ingredient quality and the sustainability issues associated with traditional livestock-based protein farming, whose production has led to environmental contamination. Examples of alternative proteins include those produced through Cellular Agriculture, plant-based proteins, insects, and fungi. Cellular agriculture products are classified into two categories: cell-based, which include cultured meat and other foods produced from animal cells grown in culture, including insect cells; and acellular, which include recombinant animal proteins and other ingredients produced in safe microbial cell factories through microbial fermentation using genetic engineering or synthetic biology. In this review, we provide current information on the environmental impact of livestock farming, offer an overview of alternative proteins with a focus on dog food, and highlight the importance of proteins in dog health. Additionally, we analyze the significance of the palatability and digestibility of alternative proteins for dogs, assess their safety, and explore their potential market in Latin America, particularly in Mexico. Finally, we share our perspective on the potential and future research opportunities for Mexico in the field of dog food made from alternative proteins, mainly acellular products.